2010
DOI: 10.1186/1471-2377-10-61
|View full text |Cite
|
Sign up to set email alerts
|

Association of childhood trauma with cognitive function in healthy adults: a pilot study

Abstract: BackgroundAnimal and human studies suggest that stress experienced early in life has detrimental consequences on brain development, including brain regions involved in cognitive function. Cognitive changes are cardinal features of depression and posttraumatic stress disorder. Early-life trauma is a major risk factor for these disorders. Only few studies have measured the long-term consequences of childhood trauma on cognitive function in healthy adults.MethodsIn this pilot study, we investigated the relationsh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

20
184
0
6

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 229 publications
(210 citation statements)
references
References 40 publications
(50 reference statements)
20
184
0
6
Order By: Relevance
“…However, our results already bear significance for the millions of children born to affected parents, considering that 14%-24% of children have a parent with a mental illness 58 and that about 3% of the population of Group of 7 countries (Canada, France, Germany, Italy, Japan, United Kingdom, United States) are affected by schizophrenia, BD and recurrent major depression (i.e., more than 20 million patients). Nevertheless, because abuse and neglect are known to have a negative influence on cognitive functioning in community samples of healthy adults 20,21 and children/ adolescents, 22,23 our results may not be specific to the genetic high-risk population. Second, although our measure of abuse and neglect had the advantage of drawing information from multiple sources and from contemporary medical records instead of only retrospective self-reporting of childhood events by adults as in most previous studies, our measure was not prospective.…”
Section: Limitationsmentioning
confidence: 84%
See 2 more Smart Citations
“…However, our results already bear significance for the millions of children born to affected parents, considering that 14%-24% of children have a parent with a mental illness 58 and that about 3% of the population of Group of 7 countries (Canada, France, Germany, Italy, Japan, United Kingdom, United States) are affected by schizophrenia, BD and recurrent major depression (i.e., more than 20 million patients). Nevertheless, because abuse and neglect are known to have a negative influence on cognitive functioning in community samples of healthy adults 20,21 and children/ adolescents, 22,23 our results may not be specific to the genetic high-risk population. Second, although our measure of abuse and neglect had the advantage of drawing information from multiple sources and from contemporary medical records instead of only retrospective self-reporting of childhood events by adults as in most previous studies, our measure was not prospective.…”
Section: Limitationsmentioning
confidence: 84%
“…Our hypothesis that childhood trauma would be responsible for the poor cognitive performance observed is supported by the literature, suggesting that childhood trauma leads to cognitive deficits. 8,[20][21][22][23][24][25] However, one might argue that cognitive deficits might increase the risk of maltreatment. Sixth, the present sample of 66 offspring was gathered from 25 of the 48 multigenerational families from the eastern Quebec catchment area; thus the representativeness of these 66 offspring with respect to those from the 23 other families would have to be confirmed.…”
Section: Limitationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although such an effect is very likely given that modifiable or stable biographical, psychological, genetic, individual and social factors are causal for the development of dementia, literature reporting on this topic is fairly inconsistent [13]. For example, in a recent study, Majer and colleagues investigated a group of healthy adults with significant exposure to early-life trauma and concluded that physical neglect and emotional abuse might be associated with long-term and working memory deficits in adulthood [14]. Since the authors did not include individuals suffering from PTSD or other traumarelated psychiatric disorders, their study does neither allow to draw conclusions on the association between these disorders and cognitive dysfunction nor does it provide information on the influence of the time-point of traumatization ( i.e.…”
Section: Introductionmentioning
confidence: 99%
“…No campo da memória, sugere-se que os prejuízos mnemônicos na vida adulta associados ao estresse precoce constituiriam um fator de risco para o desenvolvimento de psicopatologias (Majer, Nater, Lin, Capuron, & Reeves, 2010). Estudos demonstraram também que adultos com história de maus tratos podem apresentar prejuízos na memória autobiográfica, apresentando maior propensão a produzir falsas memórias e, por consequência lançando dúvidas sobre a acurácia de memória dessa população (Henderson, Hargreaves, Gregory, &Williams, 2002;Clancy, Schacter, McNally & Pitman, 2000).…”
Section: Efeitos Do Estresse Precoce Na Cogniçãounclassified